2015
DOI: 10.4236/abb.2015.65034
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Association of Arbuscular Mycorrhizal Fungi in Different Cultivars of Wheat from Lalganj Pratapgarh District of Utter Pradesh, India

Abstract: Arbuscular mycorrhizal fungi are key components of soil micro-flora and obviously interact with other microorganisms in the rhizosphere which is the zone of influence of plant roots on microbial populations and other soil constituents. Keeping in view the importance of AM fungi, the present study was undertaken for assessing the AM fungal spore population dynamics in the rhizosphere soil and its colonization in rhizosphere soils in relation to soil physico-chemical factors. Present study represents an attempt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Arbuscular mycorrhizal fungi interact at the root-soil interface in a coordinated manner. Their hyphae absorb and translocate water and nutrients from the soil to the plant to increase its growth and development (Dwivedi, 2015;Priyadharsini & Muthukumar, 2015). Wheat is colonized by mycorrhizae, but colonization depends on AMF strains and soil conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi interact at the root-soil interface in a coordinated manner. Their hyphae absorb and translocate water and nutrients from the soil to the plant to increase its growth and development (Dwivedi, 2015;Priyadharsini & Muthukumar, 2015). Wheat is colonized by mycorrhizae, but colonization depends on AMF strains and soil conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Rice is a critical source of food for more than 3 billion people annually. Rice is cultivated in 45 million hectare which is with a production of 120 million tones (Financial year 2020-2021) and productivity is 2550 kg/ha of our country" [1,2]. "Soil sodicity/salinity has become a severe threat to ensure global food security.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce environmental contamination, particularly soil pollution, most experts propose using biofertilizers in combination with inorganic fertilizers in a sustainable manner to preserve soil health, productivity, disease resistance, and yield growth 28 (Lekberg and Koids 2005). The AM fungus differs with host ranges, according to Dwivedi 29 . Despite their widespread presence, they revealed that every taxonomic group of plants and the list of species not infected is likely devoid of microorganisms such as bacteria, fungi, and actinomycetes that may aid in crop yields by assisting in the solubilization of insoluble phosphorus and encouraging plant growth by providing hormone levels, vitamins, and other growth-promoting substances.…”
Section: Introductionmentioning
confidence: 99%